Metal ion effects on Polyphenol Oxidase Covalently immobilized on a Bio-Composite - Uzunoğlu, Serap Beyaztaş; Uzunoğlu, Tayfun; Koçsuz, Samet; Evyapan, Murat; Arslan, Oktay (Cellular and Molecular Biology, 2021)
Biosensors can be developed using different immobilization methods. Interest in immobilization methods have increased because biosensors have been important for science. Polyphenol oxidase (PPO) was used generally in biosensor applications. For this purpose, Polyphenol oxidase from banana was purified and covalently immobilized on chitosan-gelatin bio-composite. The properties of immobilized enzyme were investigated and compared to free enzyme. Various parameters were studied such as pH, temperature and storage stability on immobilized and free enzyme. Kinetic parameters were also evaluated by different substrates on immobilized and free enzyme. Catechol was determined the best substrate for immobilized enzyme with optimum condition. In vitro effects of metal ions were studied on immobilized enzyme. Concentration range of metal ions is 1.0-10.0 x10-6 mol/L. The activity of immobilized PPO was increased by Fe+2 and Ag+1 ion. Co+3 and Cu+1 had very strong inhibitory effects with IC50 values of 19.69x10-3 mol/L and 23.49 x10-3 mol/L, respectively. Inhibition constants (Ki) and inhibition types of metal ions were determined with immobilized enzyme. Zn+2 and Cr+3 ions were showed competitive inhibition and Pb+2 ions were determined non-competitive inhibition with immobilized enzyme. Mixed type inhibition was obtained with Co+3 ion using catechol as substrate with 3.33x10-5 mol/L Ki value on immobilized PPO. Immobilized PPO can be evaluated for biosensor for the purpose of measurements of metal ions.